Pengaruh Gerakan Senam Asma Terhadap Penurunan Frekuensi Sesak Napas Pada Klub Asma Di RSUP Surakarta - Isnaini Herawati; Wahyu Tri Sudaryanto; Alfi Salatina; Rakhma Nur Fitratun Nikmah; Abyori Daru Murtama (Universitas 45 Surabaya, 2023)
Asthma is a chronic inflammatory condition of the airways that involves various cells and their components. This chronic inflammation can result in increased hypersensitivity in the airways, which causes recurring symptoms such as wheezing, difficulty breathing, a heavy sensation in the chest, and coughing, especially at night or early in the morning. Asthma greatly affects a person's quality of life, especially when an asthma attack occurs. Asthma attacks can cause severe shortness of breath, prolonged coughing, and chest pain. In severe cases, it can cause death if not treated quickly and appropriately. Method: This community service activity was carried out in several stages, namely as follows: 1) request for permission and interviews with asthma club administrators at RSUP Surakarta; 2) observing asthma exercise activities and collecting pre-data using a questionnaire; 3) education and justification of movements in asthma exercises; 4) post data collection using a questionnaire; 5) evaluate activities by analyzing the results of pre and post questionnaires. Results: After carrying out this activity, the results were obtained that justification of asthma exercise movements had a sufficient impact on reducing shortness of breath in asthma sufferers. Participants who regularly participate in asthma exercises experience a better quality of life.